EMT Subtype Influences Epithelial Plasticity and Mode of Cell Migration - Aiello, Nicole M.; Maddipati, Ravikanth; Norgard, Robert J.; Balli, David; Li, Jinyang; Yuan, Salina; Yamazoe, Taiji; Black, Taylor; Sahmoud, Amine; Furth, Emma E.; Bar-Sagi, Dafna; Stanger, Ben Z. (Developmental cell, 2018)
Epithelial-mesenchymal transition (EMT) is strongly implicated in tumor cell invasion and metastasis. EMT is thought to be regulated primarily at the transcriptional level through the repressive activity of EMT transcription factors. However, these classical mechanisms have been parsed out almost exclusively in vitro, leaving questions about the programs driving EMT in physiological contexts. Here, using a lineage-labeled mouse model of pancreatic ductal adenocarcinoma to study EMT in vivo, we found that most tumors lose their epithelial phenotype through an alternative program involving protein internalization rather than transcriptional repression, resulting in a “partial EMT” phenotype. Carcinoma cells utilizing this program migrate as clusters, contrasting with the single-cell migration pattern associated with traditionally defined EMT mechanisms. Moreover, many breast and colorectal cancer cell lines utilize this alternative program to undergo EMT. Collectively, these results suggest that carcinoma cells have different ways of losing their epithelial program, resulting in distinct modes of invasion and dissemination. [Display omitted] •Pancreatic carcinoma cells use two distinct programs to undergo EMT•Transcriptional repression of epithelial genes mediates EMT in a minority of tumors•Re-localization of epithelial proteins mediates EMT in a majority of tumors•Different EMT programs are associated with different modes of invasion Using a lineage-traced tumor model, Aiello et al. describe a program of epithelial-to-mesenchymal transition (EMT), conserved across several carcinomas, involving re-localization of epithelial proteins rather than transcriptional repression. This alternative program leads to a “partial EMT” phenotype that promotes collective tumor cell migration and formation of circulating tumor cell clusters.